Sistema de controle de logística de E-commec - SILVA, Rafael Lazarini Arrifano; SILVA, Douglas Soares (109, 2022)
Em um mercado competitivo a velocidade de envio de produtos da internet é um dos mais importantes elementos para se destacar no mercado. A expedição se tornou cada vez mais crucial para garantir que não aconteçam atrasos indesejados. Afirma-se que ao gerenciar a data de envio e o controle de itens enviados de forma ideal, as empresas se destacam cada vez mais em marketplaces. Dessa forma, o objetivo deste trabalho é analisar a gestão de expedição de uma empresa que atua no e-commerce. Foram utilizadas pesquisas bibliográficas para compreensão do assunto abordado.

In a competitive market the speed of internet shipping products is one of the most important elements to be highlighted in the market. Expedition has become more and more crucial to ensure that unforeseen delays do not occur. It is said that by ideally managing the shipping date and controlling the items shipped, companies increasingly stand out in marketplaces. The aim of this study is to present a solution to this need, in a simple way, adapting to the continuous flow of orders. Due to bibliographic research to understand the theme and interviews with a company that is in this context, a software integrated to the factory ecosystem was developed, which has achieved the expected results.
E-commerce logistics control system
Keywords: Contabilidade de lucros; Vendas; Logística; Comércio eletrônico; Informação e Comunicação